Behavior Problems and Psychosocial Skills in Institutionalized Children and Adolescents - Fernández-Daza, Martha P.; Doctoranda del Programa de Doctorado en Psicología Clínica y de la Salud de la Universidad de Granada. Becaria de posgrado del FONACIT (República Bolivariana de Venezuela). (Pontificia Universidad Javeriana, 2012)
The main objective of this study is analyze behavior problems of a sample of institutionalized (residential care) Venezuelan tweens and teens, ages between 11 and 16. The sample consisted of 111 participants institutionalized in civil associations and institutions state protection, and 111 matched controls from schools public and private or subsidized. The psychosocial and academic was assessed skills and internalizing and externalizing behavior problems reported by the reports of parents, carers and self reports. The Youth Self-Report (YSR) and Child Behavior Checklist (CBCL) were completed. The results of the study show that children and adolescents are less institutionalized psychosocial and academic skills, as well as, more externalized behavior problems and internalized self-reported that young people living with their parents. Parents, teachers and caregivers appreciated minor differences between the two groups. Findings obtained support the influence of early deprivation on psychosocial skills, emotional issues and behavioral in children and adolescents. It is considered that institutionalization is a risk factor for the harmonious development of young people.